PAX POST-NAPOLEONICA: RISE AND FALL OF RELATIVELY PEACEFUL PERIOD IN EUROPE (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article examines the Pax Post-Napoleonica, the period of relative stability in Europe from Napoleon’s first overthrow in 1814 to the start of the First World War in 1914. It argues that the Congress of Vienna and the Concert of Europe created a new way of managing peace through balance of power and regular consultation. However, rising nationalism, the decline of the Ottoman Empire, and growing great-power rivalry slowly weakened this system. By tracing key events from 1814 to 1914, the article shows how the post-Napoleonic peace was built, challenged, and finally brought to an end.